2017
DOI: 10.1002/jum.14250
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Dysfunction of Hypertrophic Cardiomyopathy Genotype‐Positive Subjects Without Hypertrophy Is Detected by Tissue Doppler Imaging: A Systematic Review and Meta‐analysis

Abstract: Tissue Doppler imaging-derived diastolic dysfunction can be found in HCM genotype-positive subjects without hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
1
6
0
3
Order By: Relevance
“…Generally, diastolic dysfunction with slowed relaxation and compromised ventricular filling (e.g., reviewed in Reference [173]), but not always found [173].…”
Section: Diastolic Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, diastolic dysfunction with slowed relaxation and compromised ventricular filling (e.g., reviewed in Reference [173]), but not always found [173].…”
Section: Diastolic Dysfunctionmentioning
confidence: 99%
“…Later studies reported somewhat variable results, e.g., some studies reported no clear differences in TDI-based assessment of diastolic function between mutation carriers and a control group [201,202]. More recently, a meta-analysis [173] involving the three mentioned studies and seven more suggested statistically significantly lower Ea value at the septum in mutation carriers than among individuals in the control group implying that mutation carriers generally exhibit diastolic dysfunction. The latter effect would be compatible with often (but not invariably) increased calcium-sensitivity of contraction (see above).…”
Section: Whole Hearts and Cardiac Imagingmentioning
confidence: 99%
“…Синдром дисфункции ЛЖ Диастолическая функция ЛЖ может быть нарушена уже у носителей мутации, в догипертрофической стадии ГКМП -генотип (+)/фенотип (-) [91].…”
Section: этиология и патогенез заболевания или состояния (группы заболеваний или состояний)unclassified
“…По мере прогрессирования гипертрофии, развития фиброза, нарастания степени митральной регургитации (МР), присоединения ишемии миокарда диастолические нарушения нарастают, приводя к увеличению давления в ЛП (соответственно, и к увеличению конечнодиастолического давления (КДД) ЛЖ). Также выраженная диастолическая дисфункция может приводить к развитию легочной гипертензии у некоторых пациентов (у 50% симптомных пациентов) [91][92][93][94][95][96].…”
Section: этиология и патогенез заболевания или состояния (группы заболеваний или состояний)unclassified
See 1 more Smart Citation